2019
DOI: 10.1136/bmjspcare-2018-001653
|View full text |Cite
|
Sign up to set email alerts
|

Primary palliative care research: opportunities and challenges

Abstract: IntroductionPrimary care has a central role in palliative and end of life care: 45.6% of deaths in England and Wales occur under the care of primary care teams at home or in care homes. The Community Care Pathways at the End of Life (CAPE) study investigated primary care provided for patients in the final 6 months of life. This paper highlights the opportunities and challenges associated with primary palliative care research in the UK, describing the methodological, ethical, logistical and gatekeeping challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…15 In addition to clinician gatekeeping when recruiting for research participation during sensitive consultations, palliative and end-of-life research can encounter multiple ethical challenges in conducting research with vulnerable populations. 5,[16][17][18] High-quality ethically-sound methodologies in palliative care research are needed to protect individuals but also to ensure that research is conducted in a way that serves interests of individuals, groups, and society at large. 5,19,20 To increase relevance to groups and society, patient and public can be involved in palliative care research, yet there is limited evidence to describe the best approaches for populations affected by life-limiting illnesses.…”
Section: The Importance Of Methodology To Palliative Care Research: a New Article Type For Palliative Medicinementioning
confidence: 99%
“…15 In addition to clinician gatekeeping when recruiting for research participation during sensitive consultations, palliative and end-of-life research can encounter multiple ethical challenges in conducting research with vulnerable populations. 5,[16][17][18] High-quality ethically-sound methodologies in palliative care research are needed to protect individuals but also to ensure that research is conducted in a way that serves interests of individuals, groups, and society at large. 5,19,20 To increase relevance to groups and society, patient and public can be involved in palliative care research, yet there is limited evidence to describe the best approaches for populations affected by life-limiting illnesses.…”
Section: The Importance Of Methodology To Palliative Care Research: a New Article Type For Palliative Medicinementioning
confidence: 99%
“…The study team members had access to portable computers with both electronic charts and an electronic database, which facilitated data handling. The same electronic medical record was used in all three study sites, reducing the obstacles facing many other palliative care researchers [76].…”
Section: Completeness Of Datamentioning
confidence: 99%
“…3 The outcome-oriented model of designing research with public contributions, especially those with lived experiences of the research topic, is regularly cited as improving research methods, participant information summaries, study recruitment, and retention. 1,2,5,11,12 However, there is conflicting evidence on what impact public contributions have on research outcomes or what the effective components of public contributions are. 3,10,11 PPI work is heavily promoted in research policy despite the lack of clear evidence about the nature and extent of its contribution.…”
Section: Different Approachesmentioning
confidence: 99%
“…8 Conversely, 'experienced' public representatives from established PPI groups are often easier to find and have a clearer understanding of what they are being asked to contribute to ensure the research is appropriate, robust, and makes sense to potential participants. 12 We have found that working with both 'novice' and 'experienced' public contributors ensures an optimal broad range of advice in the earlier stages of clarifying research questions and initial design issues. More detailed 'experienced' public contributor advice is particularly helpful in the later stages of refining research methods, designing participant-facing material, and subsequent interpretation of emergent data analysis and dissemination.…”
Section: Different Approachesmentioning
confidence: 99%
See 1 more Smart Citation